Knowledge and sociality: on the Institute of Education (London) as a second home (UCL Press, 2022)
I have had a close and long-standing relationship with the IOE (Institute of Education), UCL's Faculty of Education and Society (University College London, UK). In order to understand why and how for many years the IOE became my 'second home', I infuse this article with a combination of critical academic and political points and a detailed sense of personal history. In the process, I trace out the development of a number of my arguments about the relationship between knowledge, power and education. I connect this to the role of the IOE in this development, both as an institution and with regard to people with whom I had close contacts over the years. Among the people I particularly focus on is Geoff Whitty, who was a key figure in all of this.